1998
DOI: 10.5014/ajot.52.5.345
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and Misunderstanding in Occupational Forms: A Study of Therapeutic Goal Setting

Abstract: The findings underscore the importance of recognizing that occupational forms are embedded in social processes and perspectives that inevitably come into play when occupational forms are used as therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 0 publications
1
31
0
2
Order By: Relevance
“…Meaningful experiences are hermeneutic in nature and require that the occupational therapist leave behind an objectivity-seeking client -therapist relationship in favour of a more sympathetic relationship [62]. In a study reported by Kielhofner & Barrett [63], these different approaches led the occupational therapists to intensify their efforts to encourage clients towards performances that did not resonate with the clients' experiences of reality. The current paper was inspired by different authors, e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Meaningful experiences are hermeneutic in nature and require that the occupational therapist leave behind an objectivity-seeking client -therapist relationship in favour of a more sympathetic relationship [62]. In a study reported by Kielhofner & Barrett [63], these different approaches led the occupational therapists to intensify their efforts to encourage clients towards performances that did not resonate with the clients' experiences of reality. The current paper was inspired by different authors, e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Patient education can be considered essential, since the patient should be aware that part of the rehabilitation process includes decision making. [21][22][23] The patient in that way is motivated to follow treatment and take control of his/her progress. 21 The interventions mentioned above can be implemented in the multidisciplinary approach as the physiotherapy component and thus result in a comprehensive treatment approach.…”
Section: Constructing An Evidence-based Rehabilitation Strategymentioning
confidence: 98%
“…Perhaps not coincidentally, a major research and clinical effort is under way to ascertain subtle cognitive impairments earlier, to differentiate the subtypes of dementia, and to identify individual responder subtypes to available agents in a given population (e.g., Graham et al, 1997;Hageman & Arrindell, 1999;Mitnitski et al, 1997;Ritchie, 1997;Ritchie et al, 2000). And, rather than relying on those standardized, objective psychometric measures of efficacy required since 1990 by the United States Food and Drug Administration (Leber, 1990)) which was concerned that pharmaceutical companies might not be rigorous in their testing procedures, there is now a call for sensitivity to more clinically meaningful outcomes (Joffres et al, 2000;Kielhofner & Barrett, 1998;Mallinson et al, 1996). This necessarily requires a different approach to measuring outcomes.…”
Section: Harbinger Of Hope or Commodity Fetishism: "Re-cognizing" Demmentioning
confidence: 98%